Peningkatan Hasil Belajar Matematika Menggunakan Model Cooperative Learning Tipe TGT di Kelas III SDN 15 Rambatan Kabupaten Tanah Datar - Nabila, Nurul; Masniladevi; Hendri, Sherlyane; Agusti, Fardatil Aini (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to improve mathematics learning outcomes in the area measurement material through the application of the Teams Games Tournament (TGT) type Cooperative Learning model to third-grade students of SDN 15 Rambatan, Tanah Datar Regency. This study is a Classroom Action Research (CAR) conducted in two cycles, with each cycle including the planning, action implementation, observation, and reflection stages. The research subjects consisted of 10 third-grade students, with the class teacher acting as the observer and the researcher as the action implementer. Data were collected through observation, learning outcome tests, and documentation, then analyzed using qualitative and quantitative data analysis techniques through data reduction, data presentation, conclusion drawing, and percentage and average value analysis. The results showed that the quality of the lesson plan increased from 81.25% (good) in cycle I to 91.67% (very good) in cycle II. The implementation of learning aspects of the teacher increased from 83.92% to 92.85%, while the student aspect increased from 82.14% to 89.28%. Student learning outcomes also increased from an average of 73.45 in cycle I to 87.50 in cycle II. These findings indicate that the implementation of the Teams Games Tournament (TGT) Cooperative Learning model can improve the quality of the learning process and student mathematics learning outcomes in the area measurement topic.